2012
DOI: 10.1111/j.1751-1097.2012.01091.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of UV‐A Irradiance on Lipid Accumulation in Nannochloropsis oculata

Abstract: Lipids produced by microalgae can be grouped into two categories, storage lipids and structural lipids. Storage lipids are mainly triglycerides (TGs) made up of saturated fatty acids; TGs can be transesterified to produce biodiesel. Structural lipids are made of polyunsaturated fatty acids (PUFAs), which are essential nutrients for aquatic animals and humans. The objectives of this study were: (1) to determine the effect of UV-A at different levels of exposure on total lipid accumulation in Nannochloropsis ocu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…This statement agrees with the results obtained by other authors in Nannochloropsis (Forján et al. , Srinivas and Ochs ) and artic diatoms (Leu et al. ), but differs from Wang and Chai () and Arts and Rai (), who have reported that UV radiation results in the depletion of ω‐3 fatty acids in microalgae.…”
Section: Discussionsupporting
confidence: 92%
“…This statement agrees with the results obtained by other authors in Nannochloropsis (Forján et al. , Srinivas and Ochs ) and artic diatoms (Leu et al. ), but differs from Wang and Chai () and Arts and Rai (), who have reported that UV radiation results in the depletion of ω‐3 fatty acids in microalgae.…”
Section: Discussionsupporting
confidence: 92%
“…In a study carried out by Srinivas and Ochs [91] on Nannochloropsis oculata the effect of UV-A at different levels of exposure on total lipid accumulation was investigated. UV-A treatments significantly increased the PUFA (chlorophyll-specific lipid concentration) of N. oculata cells, and UV-A and decreased nutrients had a synergistic effect on lipid accumulation.…”
Section: Uv Irradiance For Lipid Inductionmentioning
confidence: 99%
“…Nannochloroposis spp. are cultivated for EPA production so as to be used in aquaculture as nutritional ingredient and in pharmaceutical sector as a bioactive ingredient for the prevention of various human diseases (Wang and Chai, 1994;Srinivas and Ochs, 2012). Concerning applications in cosmetology, only Nannochloropsis oculata extracts have been commercially used, since they were proven to have skin-tightening properties (Susan et al, 2012).…”
Section: Introductionmentioning
confidence: 99%